Projeto e validação experimental de um controlador robusto H2 aplicado a conversores Boost - Maccari Junior, Luiz Antonio (2011)
This dissertation presents as the main contribution the design and experimental validation of a robust H2 controller applied to boost converters with variations on the parameters load resistance, input voltage and operating point duty cycle. First, a polytopic model of the plant is presented, allowing to represent all the possible variations of the parameters within intervals previously established. Design conditions for a robust H2 controller, optimal under the quadratic stability, are detailed and used, allowing to efficiently calculate the controller gains. These gains are implemented with analog circuitry and the closed-loop system is tested by means of simulation and experimental results, which show a good match and illustrate a good performance. Finally, the small perturbation rejection capacity of the closed-loop system subject to parametric variations is evaluated using the H∞ guaranteed cost.